Investigations of resolution limits for indirect microwave holographic imaging - Yurduseven, Okan; Smith, David; Livingstone, Bryan; Schejbal, Vladimír; You, Zhonghui (Wiley, 2013)
This work describes how indirect holography which has previously been applied to the determination of antenna radiation patterns can be adapted for the imaging of passive objects. It provides details of how complex scattered field values can be obtained in a simple and inexpensive manner from sampled scalar intensity measurements taken over a single scanning aperture. This work uses indirect holographic techniques to image a number of simple objects including a rectangular metallic plate, a small metal plate covered by a dielectric sheet and a small metallic circular annulus. This work demonstrates that good quality images can be reconstructed from simple scalar intensity patterns. It demonstrates that clear outlines can be obtained in particular from reconstructed phase patterns and that good images can be obtained from objects with dimensions of the order of a half wavelength.
Keywords: microwave imaging; microwave holography; near-field microwave imaging; image reconstruction